Technology Acceptance and the Use of Non-Cash Payment Systems: Empirical Evidence from Generation Y and Z - Dijan Novia Saka; Muhamad Wildan Fawaid; Muhammad Ridwan Bakhtiar; Muhammad Alfasa Ilham Haq; Mahammadaree Waeno (Journal of Finance and Islamic Banking, 2025)
Purpose: This study aims to examine the determinants influencing the use of non-cash transaction services among Generation Y and Z, focusing on the application of the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Method: This research adopts a quantitative approach using convenience sampling with a total of 713 respondents. Data analysis techniques include descriptive statistics, Partial Least Square (PLS) regression, and path model analysis using SmartPLS and Microsoft Excel. Results: The results indicate that all latent variables—performance expectancy, facilitating conditions, social influence, risk perception, and trust perception—have a significant influence on the intention to use non-cash transaction services. Although effort expectancy shows a positive relationship, its effect is not statistically significant. Implication: The findings offer valuable insights for digital financial service providers and policymakers to enhance system accessibility, trust, and user convenience to encourage broader adoption among tech-savvy generations. Originality: This study contributes to the digital payment literature by integrating technological, social, and psychological factors within the UTAUT framework, specifically targeting Generation Y and Z as key demographic groups driving the future of cashless economies.